Extraction of total phenolic and total monomeric anthocyanin contents from mangosteen (garcinia mangostana L.) hull - Cheok, Choon Yoong (2012)
Mangosteen is a popular local tropical fruit because the pulp is delicious and has high value of nutrient and mineral content. However, mangosteen hull is disposed of as waste by local people due to the unpleasant taste of bitterness, though it contains total phenolic and anthocyanins which have numerous important pharmaceutical properties. Due to the remarkable relationship between total phenolic content (TPC) and total monomeric anthocyanin (TMA) with antioxidant capacity, a series of investigations were undertaken to enhance the mangosteen crude extract yields evaluated in terms of TPC and TMA. This research involved investigations from fundamental to optimization, based on hypotheses of methanol, acidic condition of extraction solvent, and the ultrasonic wave treatment could give higher extraction yield. Results were expressed in mg gallic acid/g hull powder for TPC, while for TMA, expressed in mg cy-3-glu/g hull powder. The effect of solvents, i.e. ethyl acetate, isopropanol, acetone, ethanol, methanol, and distilled water were evaluated on the extraction of total phenolic content (TPC) from mangosteen. Methanol was found as the most effective solvent in giving the highest recovery (p < 0.05) of TPC, compared to ethanol, acetone, isopropanol, ethyl acetate and distilled water. Regression equations of strong coefficients of determinations (R2  0.990) were obtained for UV-Vis spectrophotometer direct absorbance of acetone, ethanol, and methanol extracts with the Folin-Ciocalteu (FC) method, suggesting regression equations obtained can be used to determine TPC without using the FC method. The optimum conditions of extraction time, solid to solvent ratio, and methanol concentration for extraction of total phenolics from mangosteen hull powder was investigated using the response surface methodology (RSM). The experimental data obtained was adequately fitted into second-order polynomial models with R2 of 0.897. Optimal extraction parameters which gave a maximum TPC yield of 140.66 mg (gallic acid equivalent) GAE/g powder were from a 2 hours‘ extraction with 0.05 solid to solvent ratio and at 69.77% methanol concentration. Analysis using artificial neural network (ANN) predicted data which showed a higher R2 value of 0.945 and average absolute deviation values of 4.01% versus 5.37% for the RSM. This suggests that ANN is a better modeling technique for nonlinear data for predicting TPC yield extracted from mangosteen hull powder compared to the RSM. The recovery of anthocyanins from mangosteen hull was investigated using aqueous methanol solvent acidified by juice from Mexican lime (C. aurantifolia Swingle) in comparison with the conventional HCl acidified methanol solvent. The addition of 0.20 ml lime juice/ml methanol aqueous extraction solvent gave a maximum total monomeric anthocyanin (TMA) recovery of 4.742±0.590 mg cy-3-glu/g hull powder compared to 2.950±0.265 when using HCl acidified extraction solvent at 0.20%. A significant increase of 60.75% (p < 0.05) anthocyanins recovery suggests that this natural Mexican lime juice can be a good acidifying agent and replaces HCl. Particle size hull powder of 250 m to 500 m was also found to give the highest recovery of anthocyanins (p < 0.05). Two types of extraction solvents, i.e., methanol and ethanol aqueous solvent acidified with 0.20% HCl were used to investigate the effect of ultrasonication time and amplitude on TMA and TPC from mangosteen hull. The highest TMA recovery of 2.917±0.039 mg cy-3-glu/g hull powder was achieved using methanol 0.20% HCl acidified aqueous solvent with a pretreatment of an ultrasonic probe of 15 minutes‘ sonication time and 20% amplitude. While the highest recovery of TPC of 245.780±9.858 mg GAE/g hull powder was obtained using ethanol 0.20% HCl acidified aqueous solvent by pretreating the mangosteen sample with ultrasonic probe conditions of 25 minutes sonication time and 80% amplitude. In conclusion, methanol has been found to be the best extraction solvent in giving the highest TPC yield. The optimum extraction conditions of 2 hours extraction time, 0.05 solid to solvent ratio and 69.77% methanol concentration obtained from RSM gave the maximum TPC yield 140.66 mg GAE/g hull powder with an improvement of 85.41% compared to extraction with 20 hours extraction time, 0.20 solid to solvent ratio and pure methanol solvent. The extraction solvent acidified with 20 ml of Mexican lime juice gave higher TMA yield compared to HCl acidified‘s. The ultrasonication of 15 inutes and 20% amplitude gave the highest TMA recovery of 2.917±0.039 mg cy-3-glu/g hull powder using acidified methanol solvent, while 25 minutes and 80% amplitude gave the highest TPC of 245.780±9.858 mg GAE/g hull powder using acidified ethanol solvent. Overall, the extraction of TPC and TMA yields from mangosteen hull have been optimized by reducing the extraction time, solid to solvent ratio using acidified extraction solvent with ultrasonic wave treatment.